Spreminjanje podobe naselij enodružinskih hiš - Cigoj, Nika (Urbani izziv, 2008)
The design, representation, size, and organization of open spaces in residential areas of single-family houses has undergone significant change inthe last forty years. In order to identify trends and changes in the construction of settlements of single-family houses, a comparative analysis ofselected settlements in Ljubljana, Maribor, and Novo mesto was performed. Itwas determined that there has been a sharp reduction in open spaces, including planted and green areas, in these kinds of settlements. The shortageof land and the increased use of parcels with high density building projects have discouraged the development of planted areas along streets and the creation of gardens and common areas intended for socializing, playing, and recreation. The reduction of residential gardens and the increased elevation of buildings often results in the unsuitable physical appearance of new settlements as well as in the impoverished quality of life, an inevitable consequence of scarce greenery and common areas. Despite the fact that the useof open space is dependant on social conditions during various time periods, certain parameters that determine the quality of living space remain constant. Because of this, it has become increasingly urgent to dedicate thought to the planning of residential areas that gives a larger proportion oftheir area to open spaces and seeks a more appropriate balance between the market logic of urbanization and certain proscribed urban standards.
Keywords: bivalno okolje; enodružinske hiše; Ljubljana; Maribor; mesta; Novo mesto; prostorski razvoj; stanovanjske četrti; zelene površine